The role of corporate culture in performance measurement and management systems - Michaela Kotkova Striteska; David Zapletal (International Journal of Financial Studies, 2020)
Recently, there has been increasing pressure to change current performance measurement and management systems from control systems to those that support learning and continuous improvement. This change requires a specific corporate culture that supports the effective operation of performance measurement and management. This paper aims to clarify the relationship between corporate culture and performance measurement and management systems. Questionnaire survey data from Czech medium and large companies were collected and analyzed by Pearson's chi-squared test to validate the proposed hypothesis. The research findings confirmed that performance measurement and management systems of companies that devoted sufficient energy and attention to performance-driven culture are more effectively developed. Analysis of different performance-driven culture attributes revealed which are the most important ones.
Keywords: M14; 330; performance measurement system; performance management; performance-driven culture